Peran Penyuluhan Pertanian Dalam Proses Adopsi Inovasi di Desa Sadang, Kecamatan Taman, Kabupaten Sidoarjo: The Role of Agricultural Extension in the Innovation Adoption Process in Sadang Village, Taman District, Sidoarjo Regency - Fitriana, Nisa Hafi Idhoh; Setiawan, Risqi Firdaus (Jurnal Ilmiah Manajemen Agribisnis, 2023)
Disseminating innovation to farmers is the role and function of agricultural extension workers so that farmers are ready to adopt and apply agricultural technology in their farming activities to increase farmers' income and welfare. Based on these problems, researchers want to analyze the role of agricultural extension workers in the process of adopting farmer innovations in agricultural development. This study aims to understand the implementation of counseling in the field. In addition, the results of this study are to find out what roles exist in agricultural extension workers. Data collection techniques were used by distributing questionnaires to respondents and data analysis techniques using the method of determining respondents by distributing questionnaires consisting of questions grouped based on the role of agricultural extension workers and data analysis techniques using descriptive qualitative. The results showed that there were several roles of agricultural extension agents in the innovation adoption process, namely as a facilitator, as an innovator, as an educator, as a communicator, and as a motivator. It was found that the recapitulation of the role of agricultural extension workers scored 83.74% in the very agree category from the respondents. With that, it can be interpreted that agricultural extension agents can play a very good role in carrying out their duties in the innovation adoption process.